Festival Cap Go Meh Menjadi Pariwisata Budaya Yang Berkelanjutan Di Surya Kencana Bogor - Husen, M Sadam; Manurung, Tarida Marlin Surya (Jurnal Ilmiah Pariwisata Kesatuan, 2023)
The Cap Go Meh Festival is a Chinese ethnic celebration at the beginning of the year which comes from the word "Cap Go" which means "fifteenth" and "Meh" means "night", so Cap Go Meh literally means "fifteenth night". Sustainable tourism is a tourism management concept that is responsible for environmental and community economic sustainability. The Cap Go Meh tradition is a form of Chinese culture which is still developing and is celebrated every year by Chinese groups and usually holds parades, processions along the streets and lantern festivals as a form of joy for the entire Chinese community for the success of the one year that has just passed and at the same time as a moment to pray for progress in the coming years. Sustainable tourism aims to use natural resources and human resources in the long term. so Cap Go Meh literally means "fifteenth night. Sustainable tourism is a tourism management concept that is responsible for environmental and community economic sustainability. The Cap Go Meh tradition is a form of Chinese culture which is still developing and is celebrated every year by Chinese groups and usually holds parades, processions along the streets and lantern festivals as a form of joy for the entire Chinese community for the success of the one year that has just passed and at the same time as a moment to pray for progress in the coming years. Sustainable tourism aims to use natural resources and human resources in the long term. The research objective was to determine the economics of the Cap Go Meh Festival at Surya Kencana Bogor. To know the environment of the Cap Go Meh Festival at Surya Kencana Bogor. To find out the social culture of the Cap Go Meh Festival at Surya Kencana Bogor. The results of the research on the Cap Go Meh Festival at Surya Kencana Bogor have been held every 15th of the first month based on the lunar calendar which is the highlight of the Chinese New Year. The celebration, which originally meant thanksgiving for the ethnic Chinese community, has now turned into a party for the people of Bogor City. Developments that continue to be carried out during the Cap Go Meh celebration will eventually have a commercial selling point into Sustainable Tourism. The Cap Go Meh celebration, which has now been carried out openly and has become the tourism agenda for the City of Bogor, has had a positive impact on society, both culturally and economically. This shows that the Cap Go Meh celebration has experienced a process of development from year to year. Key Words : Cap Go Meh Festival and Cap Go Meh Tradition and Sustainable Tourism